Jiawei Buyang Huanwu Decoction modulates gut microbiota and metabolic profiles in a rat model of idiopathic pulmonary fibrosis - Sun, Dandan; Cao, Xinxin; Sun, Jing; Zhang, Huimin; Liu, Yujun (Frontiers in Microbiology, 2025)
IntroductionIdiopathic pulmonary fibrosis (IPF) is a progressive lung disease with irreversible fibrosis and poor prognosis. Jiawei Buyang Huanwu Decoction (JBHD) has demonstrated therapeutic effects, but the exact mechanisms, particularly those mediated by the gut microbiota, remain largely unexplored. This study aimed to explore how JBHD modulates gut microbiota, and how these changes may influence host metabolic regulation in the context of IPF.MethodsThe IPF model was established via intratracheal bleomycin injection. After 28 days of treatment, feces samples were obtained for 16S rRNA gene sequencing, whereas serum and urine samples were collected for metabolomic analyses.ResultsGut microbiota analysis showed that JBHD restored microbial dysbiosis in IPF rats. Differentially altered fecal microbes (DAFMs) reversed by JBHD included Lactobacillus, Clostridium sensu stricto 1, Turicibacter, and Christensenellaceae R-7 group at the genus level. The microbial functions reversed by JBHD in both KEGG Level 3 and COG analyses were related to amino acid metabolism, including Biosynthesis of amino acids (KEGG) and Amino acid transport and metabolism (COG). Serum and urine metabolomics showed that JBHD modified the metabolic profile of IPF rats. Among the differentially expressed metabolites (DEMs) altered by IPF, JBHD reversed 11 in serum and 13 in urine. Pathway analysis indicated that these DEMs were mainly associated with amino acid and lipid metabolism. The consistency between microbial functional predictions and host metabolomic findings in amino acid metabolism suggests that JBHD may influence host metabolic pathways through gut microbiota modulation. Functional prediction of the targets of reversed DEMs highlights signaling pathways related to immune regulation. Correlation and network analyses between DAFMs and DEMs reveal potential associations, implying that gut microbiota alterations may contribute to coordinated changes in host metabolism.DiscussionJBHD may act by reshaping specific microbial communities, which in turn could help restore related metabolic disturbances. These findings suggest a possible microbiota-mediated mechanism through which JBHD may exert its effects along the gut–lung axis.